2004
DOI: 10.1073/pnas.0403283101
|View full text |Cite
|
Sign up to set email alerts
|

The Rai (Shc C) adaptor protein regulates the neuronal stress response and protects against cerebral ischemia

Abstract: Rai (Shc C or N-Shc) is a neuron-specific member of the family of Shc-like adaptor proteins. Rai functions in the cytoplasmic propagation of Ret-dependent survival signals and regulates, in vivo, the number of sympathetic neurons. We report here a function of Rai, i.e., the regulation of the neuronal adaptive response to environmental stresses. We demonstrate that (i) primary cultures of cortical neurons from Rai ؊/؊ mice are more sensitive to apoptosis induced by hypoxia or oxidative stress; (ii) in Rai ؊/؊ m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 25 publications
2
37
0
Order By: Relevance
“…RNA Isolation, cDNA Synthesis, and Real-Time Polymerase Chain Reaction Twenty-four hours after TBI, mice were killed and ipsilateral cortices dissected for gene expression analysis as previously described (Storini et al, 2005;Troglio et al, 2004). Briefly, total RNA was obtained from tissue specimens using the Trizol reagent (Gibco BRL, Kidlington, MD, USA).…”
Section: Transferase-mediated Dutp Nick End Labeling Stainingmentioning
confidence: 99%
“…RNA Isolation, cDNA Synthesis, and Real-Time Polymerase Chain Reaction Twenty-four hours after TBI, mice were killed and ipsilateral cortices dissected for gene expression analysis as previously described (Storini et al, 2005;Troglio et al, 2004). Briefly, total RNA was obtained from tissue specimens using the Trizol reagent (Gibco BRL, Kidlington, MD, USA).…”
Section: Transferase-mediated Dutp Nick End Labeling Stainingmentioning
confidence: 99%
“…SHC3 is another candidate gene within the linked region based on its biological functions in activating the PI3K-PKB and MAPK pathways, 14,37 in regulating NMDA receptor function, 21 and the neuronal adaptive response to environmental stress. 22 In this study, 11 SNPs within SHC3, as well as the haplotypes of various combinations of these SNPs, were analyzed for associations with three adjusted ND measures in 602 nuclear families of either AA or EA origin. In light of the ethnic-specific characteristics of the SNPs among different ethnic groups 29,38 as well as known ethnic differences in ND and nicotine metabolism, 39,40 we not only performed association analysis on the combined sample (to increase power) but also on ethnicity-specific samples separately.…”
Section: Discussionmentioning
confidence: 99%
“…Such a protective effect might be explained by the stressameliorating function of SHC3. 22 For example, Troglio et al 22 reported that ShcC-null mice had significantly higher mortality, more severe neurological deficits, and increased apoptosis and size of the infarct area, compared with wild-type mice. Several epidemiological studies have documented strong associations between depression and smoking; 50,51 however, the presence of a causal relation between depression and smoking is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C Capone et al IL-1b observed as early as 24 h after injury and later on at 48 h. Instead, analysis of the expression of genes related to apoptosis (Troglio et al, 2004) revealed that 48, but not 24 h from ischemia, ST1942 decreases the expression of the proapoptotic gene Bax and increases that of the antiapoptotic Bcl-2 thus inducing a shift from a pro-to an antiapoptotic status. Notably, the decrease in Bax and the increase in Bcl-2 expression are wide and do not simply restore the expression observed in sham operated experimental groups.…”
Section: -Aminotetraline In Ischemic Injurymentioning
confidence: 98%